Question
upstudy study bank question image url

If \( y=\frac{\operatorname{cosec}\left(e^{x}\right)}{e^{x}} \) then \( \frac{d y}{d x}= \)

Ask by Washington Estrada. in Nigeria
Jan 11,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\[ \frac{dy}{dx} = -\cot(e^{x})\,\csc(e^{x}) - \frac{\csc(e^{x})}{e^{x}} \]

Solution

To find the derivative \( \frac{dy}{dx} \) of the function \( y = \frac{\csc(e^x)}{e^x} \), let's proceed step-by-step. **Step 1: Rewrite the Function** \[ y = \frac{\csc(e^x)}{e^x} = \csc(e^x) \cdot e^{-x} \] **Step 2: Apply the Product Rule** The product rule states that if \( y = u \cdot v \), then: \[ \frac{dy}{dx} = u' \cdot v + u \cdot v' \] Let: \[ u = \csc(e^x) \quad \text{and} \quad v = e^{-x} \] **Step 3: Differentiate Each Part** 1. **Differentiate \( u = \csc(e^x) \):** \[ u' = \frac{d}{dx} \csc(e^x) = -\cot(e^x) \csc(e^x) \cdot \frac{d}{dx} e^x = -\cot(e^x) \csc(e^x) \cdot e^x \] 2. **Differentiate \( v = e^{-x} \):** \[ v' = \frac{d}{dx} e^{-x} = -e^{-x} \] **Step 4: Combine Using the Product Rule** \[ \frac{dy}{dx} = u' \cdot v + u \cdot v' = \left(-\cot(e^x) \csc(e^x) \cdot e^x\right) \cdot e^{-x} + \csc(e^x) \cdot (-e^{-x}) \] **Step 5: Simplify the Expression** \[ \frac{dy}{dx} = -\cot(e^x) \csc(e^x) - \frac{\csc(e^x)}{e^x} \] **Final Answer:** \[ \frac{dy}{dx} = -\cot(e^{x})\,\csc(e^{x}) - \frac{\csc(e^{x})}{e^{x}} \] **In LaTeX:** \[ \frac{dy}{dx} = - \cot(e^{x}) \csc(e^{x}) - \frac{\csc(e^{x})}{e^{x}} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To find \( \frac{d y}{d x} \) for \( y=\frac{\operatorname{cosec}\left(e^{x}\right)}{e^{x}} \), we will use the quotient rule. The quotient rule states that if \( y = \frac{u}{v} \), then \( \frac{d y}{d x} = \frac{v \frac{d u}{d x} - u \frac{d v}{d x}}{v^2} \) where \( u = \operatorname{cosec}(e^x) \) and \( v = e^x \). First, we compute \( u \) and \( v \): - \( u = \operatorname{cosec}(e^x) = \frac{1}{\sin(e^x)} \) - \( v = e^x \) Next, we find the derivatives: - \( \frac{d v}{d x} = e^x \) - To differentiate \( u \), we use the chain rule: \[ \frac{d u}{d x} = -\operatorname{cosec}(e^x)\cot(e^x) \cdot \frac{d}{d x}(e^x) = -\operatorname{cosec}(e^x)\cot(e^x) \cdot e^x \] Now applying the quotient rule: \[ \frac{d y}{d x} = \frac{e^x \left(-\operatorname{cosec}(e^x)\cot(e^x) \cdot e^x\right) - \operatorname{cosec}(e^x) \cdot e^x}{(e^x)^2} \] This simplifies to: \[ \frac{d y}{d x} = \frac{-e^{2x}\operatorname{cosec}(e^x)\cot(e^x) - e^x \operatorname{cosec}(e^x)}{e^{2x}} \] Further simplifying gives: \[ \frac{d y}{d x} = -\operatorname{cosec}(e^x)\left(\cot(e^x) + 1\right) \] Thus, the final answer is: \[ \frac{d y}{d x} = -\operatorname{cosec}(e^x)(\cot(e^x) + 1) \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy